Water Management, Partnerships, Rights, and Market Trends An Overview for Army Installation Managers - Lachman, Beth E. (RAND Corporation, 2016)
This report assesses water management, partnerships, rights, and market trends and opportunities, and how Army installations can potentially use them to improve programs and investments in water and wastewater systems. It provides examples from across the United States, along with detailed case studies of two states and two Army installations, and recommends ways to improve installation water security, programs, and infrastructure investments.